E-Service Quality and E-Trust to E-Satisfaction in Services via the PLN Mobile Application at ULP Pangkalpinang - Sarwindah; Mariska, Salsa Asri; Marini (Universitas Mohammad Husni Thamrin, 2025)
Society's dependence on energy has resulted in an increase in society's need for and use of energy. This causes an increase in demand for superior products or services that can effectively meet consumer needs and expectations. This research aims to determine the influence of E-Trust and E-Service Quality on E-Satisfaction of PLN Mobile customers. This research uses quantitative research methods with questionnaires as data collection material which is analyzed with the help of SPSS 27 software. The sample used in this research was 99 respondents. The sample was taken from PLN Mobile application users in Pangkalpinang. The analysis techniques used are validity test, reliability test, normality test, linear test, multicollinearity test, heteroscedasticity test, multiple linear regression test, determination analysis, t-test and f-test. The analytical method used in this research is multiple linear regression analysis. The research results found show that the E-Trust, E-Service Quality variables individually or partially have a significant effect on application users' E-Satisfaction. Then the E-Satisfaction variable simultaneously has a significant effect on application users' E-Satisfaction. Based on the test results, the coefficient of determination or value (R Square) was obtained at 0.501 or 50.1%. This shows that the E-Trust, E-Service Quality variables are able to explain 50.1% of the dependent variable user E-Satisfaction. Meanwhile, the remaining 49.9% is explained or influenced by unknown variables in this study.